Strategi Coping Stress Mahasiswa Dalam Penulisan Skripsi - Made Saihu; M Adib Abdushomad; Encep Darisman (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This study aims to determine the various problems and stress coping performed by students in preparing their thesis for STIT Al-Amin Kreo Tangerang students. There are 5 (five) informants involved in this study. The research approach used a qualitative approach with data collection techniques through observation, interviews, and FGD (focus group discussion). The results showed that the problem faced by students who were writing their thesis was between happiness and stress. On the one hand, they feel happy because they have reached the final peak of activities to obtain a bachelor's degree, will finish college, graduate and be able to find work after bachelor's degree. On the other hand, feeling stressed, such as feeling overwhelmed, confused, worried, afraid, insecure, anxious, feeling helpless and helpless or pessimistic, feeling guilty, feeling worried, nervous, feeling very tense, panic, restless, feeling chaotic, arises feelings of fear and anxiety, depressed, embarrassed and sometimes sad, feels tired, tired, upset, bored, bored and feels stuck in the mind. These feelings are caused by internal and external factors. In stress coping, students have strategies that focus on the emotional realm and do not use coping that is focused on problems. A strategy that is considered effective for students in writing a thesis so that the thesis does not become a scary thing.